The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/esp.4783
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine biofilm patterns: Modern analogues for Precambrian self‐organization

Abstract: This field and laboratory study examines whether regularly patterned biofilms on present‐day intertidal flats are equivalent to microbially induced bedforms found in geological records dating back to the onset of life on Earth. Algal mats of filamentous Vaucheria species, functionally similar to microbial biofilms, cover the topographic highs of regularly spaced ridge–runnel bedforms. As regular patterning is typically associated with self‐organization processes, indicators of self‐organization are tested and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 113 publications
(277 reference statements)
4
40
0
Order By: Relevance
“…At a small scale, within the vegetation patches, flow velocities and erosion are reduced (e.g., Nepf, 2012) resulting in improved plant growth (positive feedback van Wesenbeeck et al, 2008). At a larger scale, the water is partly forced to flow around the vegetation patches, leading there to increased flow velocities (Zong & Nepf, 2010), potential erosion (Bouma et al, 2007), and to inhibition of plant growth just next to the vegetation patch (negative feedback van Wesenbeeck et al, 2008). Scale-dependent biogeomorphic feedbacks have been studied extensively over the past decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a small scale, within the vegetation patches, flow velocities and erosion are reduced (e.g., Nepf, 2012) resulting in improved plant growth (positive feedback van Wesenbeeck et al, 2008). At a larger scale, the water is partly forced to flow around the vegetation patches, leading there to increased flow velocities (Zong & Nepf, 2010), potential erosion (Bouma et al, 2007), and to inhibition of plant growth just next to the vegetation patch (negative feedback van Wesenbeeck et al, 2008). Scale-dependent biogeomorphic feedbacks have been studied extensively over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Their strength is reported to depend on many characteristics, such as patch size (Licci et al, 2019;Vandenbruwaene et al, 2011), stem density (Bouma et al, 2009), stem height (Gu et al, 2018), stem stiffness (Bouma et al, 2013;Marjoribanks et al, 2019;Ortiz et al, 2013;Schwarz et al, 2015), interpatch distance (de Lima et al, 2015;Meire et al, 2014;Vandenbruwaene et al, 2011), lateral expansion rate (Schwarz et al, 2018), and flow velocity (Bouma et al, 2013;Marjoribanks et al, 2019;Vandenbruwaene et al, 2011). Several studies have also shown that strong scale-dependent feedbacks are needed to result in the self-organization of regular spatial biogeomorphic patterns at the landscape scale (Rietkerk et al, 2004;Schwarz et al, 2018;Temmerman et al, 2007;van de Koppel et al, 2012). Given the above description of the scale dependency of biogeomorphic feedbacks, it becomes evident that their representation within numerical models is highly dependent on the grid size, which raises a balance problem between domain size and computational time.…”
Section: Introductionmentioning
confidence: 99%
“…The study of van de Vijsel et al . () reveals a striking similarity between present‐day sedimentary patterns in ridges and sedimentary patterns found in ancient stromatolites and Precambrian microbialite strata. Their laboratory study shows that biofilm sediment trapping and stabilization in ridges of present‐day intertidal flats is found to be characterized by indicators of self‐organization, suggesting an intriguing hypothesis whereby self‐organization dynamics might have been captured in fossil microbialites, a notion that may be important for paleoenvironmental reconstruction.…”
Section: Editorialmentioning
confidence: 58%
“…By analysing the effects of the impinging wind waves on the retreat of salt-marsh boundaries, and how the temporal evolution of wind-wave fields over the last centuries affects erosional dynamics, they highlight that relating salt-marsh lateral erosion rates to mean wave-power densities provides a valuable tool to address long-term tidal morphodynamics. The study of van de Vijsel et al (2020) reveals a striking similarity between present-day sedimentary patterns in ridges and sedimentary patterns found in ancient stromatolites and Precambrian microbialite strata. Their laboratory study shows that biofilm sediment trapping and stabilization in ridges of present-day intertidal flats is found to be characterized by indicators of self-organization, suggesting an intriguing hypothesis whereby self-organization dynamics might have been captured in fossil microbialites, a notion that may be important for paleoenvironmental reconstruction.…”
mentioning
confidence: 73%
See 1 more Smart Citation